An Overview Of Surgical Site Infection Treatment Guidelines (The Review of Diabetic Studies, 2025)
Surgical site infections are complications that develop post-surgery and often associated with high rates of morbidity and mortality in patients, especially in low- and middle-income countries. These infections are often fatal and thus require prompt and adequate care. Aim: To objectively review the latest methodology for treatment guidelines regarding surgical site infections.Materials and methods: This review is a comprehensive search of PUBMED from the year 2005 to 2025.Conclusion: Surgical site infection is a serious condition that is associated with high mortality and morbidity. These conditions require prompt diagnosis and appropriate management to prevent the worsening of the patient’s health and loss of life.